Successful treatment of stiff-person syndrome with plasmapheresis: case report and literature review - Nasvytis, M.; Kaladytė Lokominienė, R. (Neurologijos seminarai, 2023)
Stiff-person syndrome (SPS) is a rare neurologic disease, most often caused by autoimmune process during which antibodies against glutamic acid decarboxylase (anti-GAD65) are synthesised. The main clinical symptoms, among which are axial and proximal leg muscle stiffness and painful spasms, are often provoked by external triggers. In addition to those, the disease presents with anxiety, phobias, and other psychiatric symptoms. The most notable SPS comorbidities include temporal lobe epilepsy and type 1 diabetes mellitus. In this article, we present a clinical case of a patient illustrating the course of the disease, diagnostic difficulties, and treatment options, all of which are discussed in the literature review.